Development and validation of the Screen Dependency Scale (SDS) among pre-school children - Abdul Hadi, Azwanis; Roslan, Siti Ruziana; Mohammad Aidid, Edre; Abdullah, Nurzulaikha (Academy of Family Physicians of Malaysia and Family Medicine Specialist Association of Malaysia, 2021)
Introduction: Excessive screen time in young children is associated with many harmful consequences including screen dependency. Research have shown worrying prevalence of media related dependency among adolescents but questionnaires among pre-school children specifically is lacking which explains the paucity of data in this group. This study aimed to develop and validate a questionnaire to assess screen dependency among pre-school children aged 4 to 6 years old. Methods: A cross sectional 2-phase study was carried out. During Phase 1, a preliminary parent report measure questionnaire was developed in Bahasa Malaysia. It was sent to four experts for content validity followed by face validity. In Phase 2, a total of 386 parents of pre-school children aged 4 to 6 years old, split into two samples, were involved in the field study for exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Results: Sample 1 was used to perform EFA to determine the factorial structure of the SDS. All items with factor loading of > 0.4 were included. Sample 2 was used to perform the CFA and RMSEA, GFI and CFI analysis showed that the SDS has a good fit and confirms the dimensional structure found via EFA. The final questionnaire consists of 15 items with 4 factors structure and has an excellent internal consistency reliability of 0.899. Conclusion: The Screen Dependency Scale (SDS) is a reliable and valid questionnaire to detect screen dependency among preschool children ages 4 to 6 years old in Malaysia